Self-regulated learning and instructional strategies at university level - Daura, Florencia Teresita (2017)
The present study seeks to identify the personalized classroom instruction strategies teachers use to encourage student self-regulation, as well as to construct a theoretical framework to interpret the development of the teacher student relationship at university level. A qualitative design has been adopted, with non-participant classroom observation focusing on ten subject-based courses included in the clinical course taught in Argentine medical schools. A Grounded Theory (Strauss and Corbin, 1998) analysis of the data gathered has yielded four categories: two associated with self-regulated learning and two with personalized instruction strategies. A core category has been established, which we call personalising learning co-regulating spiral. The subcategories found were quantified in order to triangulate the information obtained by the qualitative analysis.